OTAC: Optimization of Antibiotic Therapy in Critically ill Patients. Using beta-lactam antibiotics by continuous infusion - Erika Esteve-Pitarch; Ariadna Padullés-Zamora; Kristel Maisterra-Santos; Sara Cobo-Sacristán; Helena Colom-Codina (Farmacia Hospitalaria)
Objective: To determine the percentage of patients given standard doses of piperacillin/tazobactam or meropenem by continuous infusion who achieved the target pharmacokinetic/pharmacodynamic (PK/PD) index, which was defined as free concentrations four times more than the minimum inhibitory concentration (CMI) for 100% of the dosing interval (100% fT≥ 4 x MIC). Method: Preliminary data from a larger prospective clinical study analysing the PK/PD behaviour of β-lactams antibiotics continuous infusion (CI) in critical patients. The study was conducted in the intensive care units of a tertiary university hospital for adults (June 2015-May 2017). Inclusion criteria: normal renal function (glomerular renal function (GFR) CKD-EPI formula ≥ 60 mL/min/1.73 m2) and treatment with standard dose β-lactams CI. Concentrations at steady state (Css) conditions were determined using UHPLC-MS/MS. We selected the highest susceptible MIC for all likely organisms according to European Commitee on Antimicrobial Susceptibility Testing’s (i.e. piperacillin/tazobactam: 8 mg/L for enterobacteriaceae and 16 mg/L for Pseudomonas aeruginosa; meropenem: 2 mg/L for any microorganism). In addition, a subanalysis of patients was conducted using actual MIC values. Results: 61 patients were enrolled (25 to meropenem and 36 to piperacillin/tazobactam). Average age was 59 (15) years and median GFR rate was 95 mL/min/1.73 m2 (83-115). Median meropenem and piperacillin free concentrations were 16 mg/L (11-29) and 40 mg/L (21-51), respectively. 88% of patients treated with meropenem reached the PK/PD target, without differences between both microorganisms. For piperacillin/tazobactam, 61% and 11% of patients reached the target, with enterobacteriaceae and Pseudomonas as suspected microorganisms, respectively. The pathogen was isolated in 35 (57%) patients: 94% reached the target PK/PD, without differences between both antibiotic therapies. Conclusions: Standard doses of meropenem CI are sufficient to achieve a PK/PD target of 100% fT≥ 4 x MIC in suspected infections with high MICs (Pseudomonas aeruginosa or enterobacteriaceae). However, higher doses of piperacillin/tazobactam could be considered to achieve this goal. In patients with isolated microorganisms, a standard dose of both antibiotic therapies would be sufficient to achieve the target. Therapeutic drug monitoring is highly recommended for therapeutic optimization.